1999
DOI: 10.1016/s0928-8244(98)00146-1
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant and protective properties of native and recombinant Bordetella pertussis adenylate cyclase toxin preparations in mice

Abstract: Bordetella pertussis produces a cell-invasive adenylate cyclase toxin which is synthesised from the cyaA gene as an inactive protoxin that is post-translationally activated by the product of the cyaC gene. Purified active and inactive CyaA proteins were prepared from B. pertussis or from recombinant Escherichia coli expressing both cyaA and cyaC genes or the cyaA gene alone. respectively. In addition, a hybrid toxin (Hyb2) in which an internal region of CyaA had been replaced with the analogous region from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
3

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 22 publications
1
22
3
Order By: Relevance
“…We and others have previously shown that CyaA of B. pertussis is an effective vaccine adjuvant in vivo, enhancing Ab responses to coadministered Ags (7)(8)(9)(10). Our studies also demonstrated that CyaA promotes Th2 and type 1 regulatory T (Tr1) cell responses to coadministered Ags (9).…”
supporting
confidence: 68%
“…We and others have previously shown that CyaA of B. pertussis is an effective vaccine adjuvant in vivo, enhancing Ab responses to coadministered Ags (7)(8)(9)(10). Our studies also demonstrated that CyaA promotes Th2 and type 1 regulatory T (Tr1) cell responses to coadministered Ags (9).…”
supporting
confidence: 68%
“…To design future vaccines that minimize subclinical disease and reduce transmission to susceptible infants, it is crucial to understand the roles played by various protective antigens. ACT has been shown to be protective in animal models and is immunogenic in humans (15,16,40,64,65). Because ACT activities hinder local anti-bacterial immune responses (66 -68), anti-ACT antibodies may protect these cells, indirectly facilitating bacterial elimination.…”
Section: Discussionmentioning
confidence: 99%
“…31,32 Therefore, it is the high time to review the antibody responses of DTaP to other antigens including AC and ascertain their role for inclusion in DTaP along with PT, PRN and FHA. Moreover, the reports of AC of B.pertussis as an effective vaccine adjuvant in vivo, enhancing Ab responses to co-administered Ags 33,34 and; induction of Th2 and regulatory T cells response 35 further qualifies AC as strong vaccine candidate.…”
Section: Passive-protection Testmentioning
confidence: 99%